Modelling disturbances in early sensory processing in schizophrenia - Popovych, S.; Küpper, T.; Müller, R.; Brockhaus-Dumke, A. (Mitteilungen der Gesellschaft für Angewandte Mathematik und Mechanik, 2009)
Recent results suggest that disturbances of information processing within the thalamo‐cortical circuit are central in the pathophysiology of schizophrenia. We derive a mathematical model based on phase oscillators to describe the neural activity within the thalamo‐cortical loop and show that the results derived from the corresponding equations coincide with experimental data obtained by EEG measurements. It is an important advantage of the mathematically based approach that information concerning activities in deeply localized brain areas which are not directly accessible to measurements becomes available. The mathematical model describes differences between healthy subjects and patients with schizophrenia by various states of phase locking between different brain areas involved (© 2009 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)